Ben cao gang mu. 16th century Chinese encyclopedia of materia medica and natural history - Li, Shizhen, 1518-1593 (University of California Press, 2021)
Volume VIII in the Ben cao gang mu series offers a complete translation of chapters 38 through 46, devoted to clothes, utensils, worms, insects, amphibians, animals with scales, and animals with shells. The Ben cao gang mu is a sixteenth-century Chinese encyclopedia of medical matter and natural history by Li Shizhen (1518-1593). The culmination of a sixteen-hundred-year history of Chinese medical and pharmaceutical literature, it is considered the most important and comprehensive book ever written in the history of Chinese medicine and remains an invaluable resource for researchers and practitioners. This nine-volume series reveals an almost two-millennia-long panorama of wide-ranging observations and sophisticated interpretations, ingenious manipulations, and practical applications of natural substances for the benefit of human health. Paul Unschuld's annotated translation of the Ben cao gang mu, presented here with the original Chinese text, opens a rare window into viewing the people and culture of China's past.
Keywords: Materia medica -- China -- Early works to 1800.; Medicine, Chinese -- Early works to 1800.; Natural history -- China -- Pre-Linnean works.; Matière médicale -- Chine -- Ouvrages avant 1800.; Médecine chinoise -- Ouvrages avant 1800.; Sciences naturelles -- Chine -- Ouvrages prélinnéens.; MEDICAL / Acupuncture.; Materia medica; Medicine, Chinese; Natural history; China; Early works